Synergy of the young generation in prioritizing the use of Indonesian in public spaces - Rusdiono Rusdiono; Fuzy Firda Zhan; As’ad Albatroy Jalius; Dina Nur Shadrina (University of Merdeka Malang, 2024)
Indonesia is an archipelagic country with ethnic and linguistic diversity. Through the Sumpah Pemuda (Youth Pledge), the Indonesian people agreed on Indonesian as a unified language to facilitate communication between people who have different local languages. However, in the current era of globalization, the existence of the Indonesian language is starting to be eroded. Many foreign languages are preferred in public spaces. Even though this is not in line with the mandate of the Indonesian constitution. Therefore, strengthening efforts are needed through the synergy of the younger generation in prioritizing the Indonesian language in public spaces through community service activities. This activity was carried out targeting the younger generation of 11th-grade students of SMA Negeri 1 Sungai Raya in Kubu Raya Regency as many as 30 people, through socio-political studies that focus on regulations and synergy. The forms of activity used in implementing this activity are in the form of giving a pre-test, giving material and face-to-face discussions accompanied by practice, and giving a post-test. The result of this activity is an increased understanding of the younger generation regarding the constitutional mandate of prioritizing the Indonesian language in public spaces through synergy between the younger generation and synergy between related actors such as the government, business sector, media, and academics.